2017
DOI: 10.1016/j.pharep.2016.12.013
|View full text |Cite
|
Sign up to set email alerts
|

C-phycocyanin suppresses transforming growth factor-β1-induced epithelial mesenchymal transition in human epithelial cells

Abstract: The overall data suggested that C-PC suppresses TGF- β1-induced EMT and warrants further in vivo studies for future evaluation of C-PC as a potential antifibrotic agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 21 publications
0
16
0
1
Order By: Relevance
“…Recently, some researches had found that C-phycocyanin could inhibit epithelial–mesenchymal transition (EMT) by down-regulating the expression of vimentin, type 1 collagen and fibronectin, and up-regulating the expression of E-cadherin in TGF-β1-treated cells [ 26 ]. Thus, we wanted to determine the effects of C-phycocyanin on the migration of breast cancer MDA-MB-231 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, some researches had found that C-phycocyanin could inhibit epithelial–mesenchymal transition (EMT) by down-regulating the expression of vimentin, type 1 collagen and fibronectin, and up-regulating the expression of E-cadherin in TGF-β1-treated cells [ 26 ]. Thus, we wanted to determine the effects of C-phycocyanin on the migration of breast cancer MDA-MB-231 cells.…”
Section: Resultsmentioning
confidence: 99%
“…C-phycocyanin inhibited EMT by reducing the expression of vimentin, type 1 collagen and fibronectin, and increasing the expression of E-cadherinin in TGF-β1-treated cells. Thus, C-phycocyanin inhibited TGF-β1-induced EMT, so C-phycocyanin might be a potential anti-fibrosis drug 74 .…”
Section: Phycocyanin and Cancermentioning
confidence: 97%
“…Phycocyanin can promote animal blood cell regeneration, improve lymphocyte activity and lymphatic system to improve immune function, and comprehensively enhance the disease resistance of the body 73 . In addition, C-phycocyanin could inhibit TGF-β1-induced EMT and C-PC might be a potential anti-fibrosis drug 74 .…”
Section: Phycocyanin: General Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, this active compound of Spirulina extract can inhibit EMT and decrease cancer cells mobility and invasion. (Jiang et al, ; Pattarayan, Rajarajan, Ayyanar, Palanichamy, & Subbiah, ) Cyclooxygenase‐2 (COX‐2) plays critical role in cancer cells metastasis. The expression of COX‐2 was positively correlated with tumor invasion, metastasis, and poor prognosis in different cancers.…”
Section: Discussionmentioning
confidence: 99%